Pengaruh Kemampuan Mengenal Huruf Abjad Melalui Pin Activity Terhadap Perkembangan Kognitif Anak Studi Kasus di TK IT Al Mardia Desa Batang Bulu Baru - Nurmaida Nasution; Mira Yanti Lubis; Hopman Daulay (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Education is a human activity and effort to improve his personality by developing his personal potential, namely spiritual (thinking, intention, feeling, image and conscience) and physical (five senses and skills). This research aims to: (1) To find out how children's cognitive development is in recognizing the letters of the alphabet at Al Mardia IT Kindergarten, Batang Bulu Baru Village. (2) To find out how pin activity influences children's cognitive development in recognizing letters of the alphabet at Al Mardia IT Kindergarten, Batang Bulu Baru Village. This study uses a quantitative approach. The data collection techniques used are observation, documentation and tests. The sample in this study was 25 children consisting of 11 boys and 14 girls with data analysis techniques using normality tests, homogeneity tests and hypothesis tests. Based on the results of research carried out by researchers, it can be concluded that Pin activity has a significant effect on children's cognitive development in recognizing letters of the alphabet at Al Mardia IT Kindergarten, Batang Bulu Baru Village. Based on these data, Tcount is greater than Ttable or (6.51 > 1.71), so Ha is accepted and Ho is rejected. So it can be concluded that there is a significant influence of pin activity on children's cognitive development in recognizing letters of the alphabet at Al Mardia IT Kindergarten, Batang Bulu Baru Village.